DRUG DESIGN EFFORTS TOWARD AURORA KINASE INHIBITORS (REVIEW) - C.N. DIPKE; RENU VYAS (International Journal of Pharma and Bio Sciences, 2014)
In the recent years Aurora kinases have attracted increasing attention as serine/threonine kinases with various roles in cell division, including chromosomal agglutination and segration functions of centromeres, centrosomal maturation, spindle formation and cytokinesis. overexpressed aurora kinases are recently studied and have shown their involvement in oncogenesis and aberrant increase in centrosome number emergence of polykaryocytes and failures of cancer inhibition mechanisms. Several aurora kinase inhibitions have been studied in vitro and in vivo. A number of new aurora kinase inhibitors are being development of numerous aurora kinase inhibitors is likely to increase the number of selectable drugs during treatment. This review showed that different methodology toward the development of aurora kinase inhibitors.